2013
DOI: 10.1007/s10735-013-9517-4
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of SGTB is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide

Abstract: SGTB (Small glutamine-rich tetratricopeptide repeat (TPR)-containing, β) plays a critical role in protein-protein interactions. The interaction between SGTB and heat shock cognate protein (Hsc70)/heat shock protein (Hsp70) has aroused much attention in recent years. The present study was designed to elucidate dynamic changes in SGTB expression and distribution in the cerebral cortex in a lipopolysaccharide (LPS)-induced neuroinflammation rat model. It was found that SGTB expression was increased significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…5A). SGTB plays a crucial role in mediating cell apoptosis via the caspase-3-dependent pathway29. In this study, we also observed up-regulated expression of SGTB, targeted by miR-133a-3p, miR-181a-5p, miR-409-5p, and miR-542-3p, at both the transcriptional and protein levels in Sertoli cells following exposure to MC-LR (Supplementary Figure S1B and Fig.…”
Section: Resultssupporting
confidence: 69%
“…5A). SGTB plays a crucial role in mediating cell apoptosis via the caspase-3-dependent pathway29. In this study, we also observed up-regulated expression of SGTB, targeted by miR-133a-3p, miR-181a-5p, miR-409-5p, and miR-542-3p, at both the transcriptional and protein levels in Sertoli cells following exposure to MC-LR (Supplementary Figure S1B and Fig.…”
Section: Resultssupporting
confidence: 69%
“…In the present study, miR‐142‐5p is revealed to target SGTB. As reported previously, up‐regulation of SGTB is related to neuronal apoptosis after neuroinflammation . In osteoarthritis, the pro‐apoptotic role of SGTB for chondrocytes has been demonstrated .…”
Section: Discussionsupporting
confidence: 66%
“…As reported previously, up-regulation of SGTB is related to neuronal apoptosis after neuroinflammation. 36 In osteoarthritis, the pro-apoptotic role of SGTB for chondrocytes has been demonstrated. 23 Functional assays in the present study described the antiproliferation and pro-apoptosis role of SGTB.…”
Section: The Regulatory Axis Of Xist/mir-142-5p/sgtb In Il-1β-inducmentioning
confidence: 99%
“…In CD8+ cells, we identified two significant differentially expressed transcripts at T6 versus controls, SGTB and FCGR3A . Little is known about SGTB but it has been associated with neuronal apoptosis after neuroinflammation [ 18 ]. Interestingly, FCGR3A encodes CD16a, which forms part of the Fc receptor of the immunoglobulin complex and interacts with a number of immune-related proteins including CD4 and PTPRC, a protein required for T-cell activation.…”
Section: Discussionmentioning
confidence: 99%